Implementación de un modelo de planeación estratégica para una empresa de servicios de construcción (2021)
Through a case study, the purpose of this article is to propose a strategic planning model to determine the policies and methodology for a services company ―a family business with 14 years of experience, which provides maintenance and construction solutions for industrial, institutional and residential infrastructure― to have a clear a roadmap to follow, based on its experience and the management model it has carried out. This work corresponds to the need of said company for a strategic planning model that allows it to explore new goals. The importance of longterm thinking has been identified, in order to enhance its strengths and take advantage of the opportunities offered by the environment, as well as to recognize and face the threats of the sector and minimize the weaknesses that arise within the organization.